Beneficiary Participation in Non-Governmental Development Organisations: A Case Study in Vietnam. Issue 10 (2nd October 2016) - Mercelis, Fleur; Wellens, Lore; Jegers, Marc
Abstract: Beneficiary participation in development projects has been an important topic of debate during the last decades. In the empirical research on the matter beneficiaries themselves are seldom, if ever, asked about their perceptions of participatory mechanisms in place. We present such a (case) study on the Vietnamese local office of a European non-governmental development organisation, also probing into other stakeholders' perceptions (46 interviews in total). Our observations allow us to refine some aspects of the extant theoretical insights on beneficiary participation and representation, as well as to formulate some recommendations for organisations aiming at increasing beneficiary participation in their decision-making.